(untitled) (Proceedings of Southern Federal University. Philology, 2021)
Ekaterina V. Ogoltseva (Moscow, Russian Federation) The article presents a philological analysis of the story by V.G. Rasputin “Money for Maria”. The author sees the task of such an analysis in a harmonious combination of elements of literary and linguistic approaches. The subject of the research is a system of linguistic means of different levels, united around the dominant psychological characteristics of the main character – the state of anxiety and expectation. The motif of uncertainty is considered as the central in the story with a number of semantic associated oppositions: light – darkness, dream – reality, own – someone else’s, peace – anxiety, real – unreal. It is shown that the whole system of pictorial means of the story correlates with these oppositions. It is identified such key imagessymbols as wind, money, snow, etc. Elements of the “form” – the twists and turns of the plot, features of the composition, the lack of resolution of the event conflict, the entire system of linguistic expressive means – serve to express a borderline, a turning point in the fate of the main characters. The article considers syntactic, morphological, word-forming means associated with the hierarchical system “motive – semantic oppositions – key images-symbols”. The approach presented in the article contributes to the most accurate interpretation of the author’s artistic intention. The text of the story appears, on the one hand, as a complex aesthetic phenomenon, and on the other, as a specially organized system of linguistic means, subordinated to the author’s intention. Key words: motif, image, symbol, linguostylistic analysis, psychological characteristics, stylistic device. DOI 10.18522/1995-0640-2021-2-133-146